2020
DOI: 10.1016/j.fm.2019.103284
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the glutamate decarboxylase system in Listeria monocytogenes; protection against oxidative stress

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…It has been found that glutamic acid plays an active role in promoting the TCA cycle in the extensive metabolism process of bacterial cells. 31,32 Similarly, in this study, we found that the proteins (GdhA, GltB, GltD, AegA, GadA, and GadB) related to glutamate metabolism were significantly up-regulated. In addition, we noticed that the expression levels of proteins (AspA, AsnA, and AsnB) involved in aspartic acid metabolism were also up-regulated.…”
Section: Resultssupporting
confidence: 75%
“…It has been found that glutamic acid plays an active role in promoting the TCA cycle in the extensive metabolism process of bacterial cells. 31,32 Similarly, in this study, we found that the proteins (GdhA, GltB, GltD, AegA, GadA, and GadB) related to glutamate metabolism were significantly up-regulated. In addition, we noticed that the expression levels of proteins (AspA, AsnA, and AsnB) involved in aspartic acid metabolism were also up-regulated.…”
Section: Resultssupporting
confidence: 75%
“…These data were in agreement with the previous observations that the antibacterial activity of benzydamine was strengthened in the alkaline conditions and the genes associated with acid resistance were downregulated. Recently, several studies reported that GAD systems, which were downregulated in the combination group, play a critical role in protecting bacteria against oxidative stress 35 , 36 , we hypothesized that the potentiation of benzydamine to antibiotics may also correlate to enhanced oxidative damage. Thus, we tested the generation of reactive oxygen species (ROS) 37 in E. coli B2 treated by either benzydamine or in combination with doxycycline.…”
Section: Resultsmentioning
confidence: 96%
“…It implies that an ancestral strain of EG007 may have originally acquired the operon by HGT from other GABA-producing microorganisms. According to previous findings, it has been reported that strains from L. monocytogenes , L. lactis , E. faecium were capable of producing GABA 72 74 . Furthermore, since microorganisms are able to raise the cytoplasm and extracellular pH by exporting the produced GABA, it is speculated that having the GAD system can be also beneficial for the microbe itself, by allowing them to survive better under acidic conditions 75 .…”
Section: Resultsmentioning
confidence: 78%